2016
DOI: 10.1371/journal.pone.0164844
|View full text |Cite
|
Sign up to set email alerts
|

Biological Interactions and Simulated Climate Change Modulates the Ecophysiological Performance of Colobanthus quitensis in the Antarctic Ecosystem

Abstract: Most climate and environmental change models predict significant increases in temperature and precipitation by the end of the 21st Century, for which the current functional output of certain symbioses may also be altered. In this context we address the following questions: 1) How the expected changes in abiotic factors (temperature, and water) differentially affect the ecophysiological performance of the plant Colobanthus quitensis? and 2) Will this environmental change indirectly affect C. quitensis photochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 66 publications
3
42
0
1
Order By: Relevance
“…Around the world, climate change has had significant direct and indirect impacts on terrestrial species, by being a major cause of speciation and species extirpation (Pound & Salzmann, 2017). Many studies have recently focused on the ecological (Etterson & Mazer, 2016;Wikelski & Tertitski, 2016), ethological (Munoz, Marquez, & Real, 2015) and biological changes (Torres-Diaz et al, 2016;Hulme, 2016) in relation to climatic change. For example, various ecosystems are vulnerable to climate change which may induce a broad array of adverse effects such as disturbances of phenological events, food web disruptions, pathogens and disease spread and ultimately, in worst case scenarios, may include extinction risks (Wu, Lu, Zhou, Chen, & Xu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Around the world, climate change has had significant direct and indirect impacts on terrestrial species, by being a major cause of speciation and species extirpation (Pound & Salzmann, 2017). Many studies have recently focused on the ecological (Etterson & Mazer, 2016;Wikelski & Tertitski, 2016), ethological (Munoz, Marquez, & Real, 2015) and biological changes (Torres-Diaz et al, 2016;Hulme, 2016) in relation to climatic change. For example, various ecosystems are vulnerable to climate change which may induce a broad array of adverse effects such as disturbances of phenological events, food web disruptions, pathogens and disease spread and ultimately, in worst case scenarios, may include extinction risks (Wu, Lu, Zhou, Chen, & Xu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Antarctica is one of the regions on the planet with extreme environment [1]. The establishment and survival of living organisms are limited by conditions such as low temperature and nutrient availability, strong winds, high sublimation and evaporation, frequent freezing-thawing cycles, low annual precipitation, high solar incidence and ultraviolet radiation, and low water availability [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this particular combination of environmental stresses is expected to favors symbiotic associations between soil microorganisms and Antarctic vascular plants though natural selection. A growing number of studies have shown that plant-microorganism’s mutualisms are common at extreme environments such as deserts (Oelmüller et al, 2009; Sangamesh et al, 2018), high-mountain (Molina-Montenegro et al, 2015; Kotilinèk et al, 2017) or polar ecosystems (Upson et al, 2009b; Newsham, 2011a; Torres-Díaz et al, 2016), for which those microbial symbionts appear to be great candidates for biotechnological applications (Khan et al, 2013; Rho et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As they did also here, those endophytes improved plant physiological parameters (i.e., A max and WUE) and the accumulation of the amino acid proline (Molina-Montenegro et al, 2016a), an osmotic molecule that has been previously associated to other symbionts conferring plant tolerance to water deficit (Nagabhyru et al, 2013; Ortiz et al, 2015). Interestingly, the beneficial effects of these Antarctic fungal endophytes seems to be ubiquitous as they are also able to establish functional symbioses with plant species from phylogenetically unrelated plant families such as the native Antarctic vascular plant Colobanthus quitensis (Torres-Díaz et al, 2016), three endangered shrubs from semiarid environments Flourensia thurifera (Asteraceae), Puya berteroniana (Bromeliacae) and Senna cumingii (Fabacae) (Molina-Montenegro et al, 2016b; Fardella et al, 2014) and the endangered south American tree Nothofagus alessandrii (Torres-Díaz, unpublished results).…”
Section: Discussionmentioning
confidence: 99%